2015
DOI: 10.1111/ecaf.12107
|View full text |Cite
|
Sign up to set email alerts
|

Regulating Work: Measuring the Scope and Burden of Occupational Licensure Among Low‐ and Moderate‐Income Occupations in the United States

Abstract: This study examines the scope and burden of occupational licensing laws in the United States for 102 low-and moderate-income occupations. Findings indicate that the licences studied require of aspiring workers, on average, $US209 in fees, one exam, and about nine months of education and training, plus minimum grade and age levels. Data also indicate striking disparities in requirements within and between occupations and within and between states. These inconsistencies likely reflect not the relative public hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 40 publications
0
18
0
Order By: Relevance
“…In a prior issue of this journal, my co‐authors and I reported the results of our analysis of the extent of, and burdens associated with, government‐mandated occupational licences for 102 low‐ to moderate‐income occupations in all 50 states and the District of Columbia in the United States (Carpenter et al ). Those results were based on data collection that ended in 2012.…”
Section: Introductionmentioning
confidence: 99%
“…In a prior issue of this journal, my co‐authors and I reported the results of our analysis of the extent of, and burdens associated with, government‐mandated occupational licences for 102 low‐ to moderate‐income occupations in all 50 states and the District of Columbia in the United States (Carpenter et al ). Those results were based on data collection that ended in 2012.…”
Section: Introductionmentioning
confidence: 99%
“…Scholars of this strand doubt that legislators intend to protect consumers and see the regulation of occupations merely as an act of unnecessary government intervention (Angrist and Guryan 2008;Arias and Scafidi 2009;Kleiner and Krueger 2010). The asserted arbitrariness of licensing within the U.S. labor market across states is taken as evidence for that view (Carpenter et al 2015). Some occupations are regulated in some states but not in others.…”
Section: The Common Reasoning About Licensing and Wagesmentioning
confidence: 99%
“…For example, in some States, an occupational license is necessary to work as a florist or an interior decorator. These unnecessary licensing requirements create a burden for workers, particularly for those with fewer means (Kleiner 2000;2015;Carpenter et al 2015). State-level reforms of occupational licensing would help make it easier for people who lose one job to move to a new one, possibly in a new location, and a number of States have begun to take action in this area.…”
Section: Creating Flexibility For Workers In the Labor Marketmentioning
confidence: 99%